(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The study mainly aimed at identifying the extent to which continuous improvement is applied at Al-Manara Private University, the degree of employees’ awareness of its importance in developing the work environment, and studying the possibilities available for its application. The descriptive analytical approach was relied upon, and the questionnaire was used as a basic tool for obtaining information. The questions included all workers in the directorates of Al-Manara Private University. The study yielded several results, including a high degree of awareness among employees at Al Manara University regarding the concept and importance of continuous improvement in developing the work environment. Information to its users in a timely manner. The study recommended the need to adopt the Kaizen strategy for continuous improvement because of its effective role in improving and developing the work environment with the least possible time and effort, and paying attention to training workers on issues related to quality, and allocating financial resources for the training process.